Magnetic multi-effect titanium-coated iron amphiphilic particle as well as preparation method and application thereof

By using magnetic multi-performance titanium iron-clad nitride particles, the partially hydrolyzed polyacrylamide is used to absorb and migrate and capture partially hydrolyzed polyacrylamide, the complex and cumbersome problem of treating oil-containing sewage in the prior art is solved, and efficient and economical sewage treatment is achieved.

CN119701885AActive Publication Date: 2025-03-28CHINA PETROLEUM & CHEMICAL CORP +2

Patent Information

Application Number
CN202311268061.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-09-27
Publication Date
2025-03-28
Estimated Expiration
2043-09-27

AI Technical Summary

Technical Problem

In the prior art, the method of treating partially hydrolyzed polyacrylamide oil-containing wastewater is complicated and cumbersome, and the cost is high, making it difficult to achieve simple and effective treatment.

Method used

Magnetic multi-performance titanium iron-clad nitride particles are used. The titanium dioxide shell is coated with the core of magnetic Fe3O4 particles. The outer surface of the shell has hydrophilic and hydrophobic parts. The inner surface is grafted with polydiethylaminoethyl methacrylate (PDEAEMA), and the adsorption and migration capture of partially hydrolyzed polyacrylamide is achieved through the micro-porous structure.

Benefits of technology

Efficient adsorption and migration capture of partially hydrolyzed polyacrylamide is achieved, simplified sewage treatment process, reduced material costs, and particles can be reused due to the pH sensitivity of PDEAEMA.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0004475231020000181
    Figure BDA0004475231020000181
  • Figure BDA0004475231020000182
    Figure BDA0004475231020000182
Patent Text Reader

Abstract

The invention relates to the technical field of sewage treatment, and provides a magnetic multi-effect titanium-coated iron amphiphilic particle as well as a preparation method and application thereof. The particle comprises a magnetic Fe3O4 particle inner core and a titanium dioxide shell layer separated from the magnetic Fe3O4 particle inner core in a core-shell mode, the outer surface of the titanium dioxide shell layer comprises a hydrophilic part and a hydrophobic part, the inner surface of the titanium dioxide shell layer and the surface of the magnetic Fe3O4 particle inner core are grafted with poly (diethylaminoethyl methacrylate), and the titanium dioxide shell layer is of a fine hole structure. The particles provided by the invention have excellent emulsifying performance, liquid drops stabilized by the particles can be controlled by an external magnetic field, and enrichment and migration of oil drops are realized, so that oil-water separation is realized; meanwhile, partial hydrolyzed polyacrylamide can be selectively adsorbed, and oily sewage containing partial hydrolyzed polyacrylamide can be efficiently treated in one step; the titanium dioxide shell layer on the surface of the particle can effectively improve the acid resistance and alkali resistance of the amphiphilic particle.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of sewage treatment, and more specifically to a magnetic multi-functional titanium-coated iron amphiphilic particle and a preparation method and application thereof. Background Art

[0002] Polymer flooding is an oil recovery method that adds a small amount of water-soluble high molecular polymer to the injected water to improve the mobility ratio and the sweep coefficient by increasing the viscosity of the water phase and reducing the permeability of the water phase, thereby increasing the crude oil recovery rate. It has become one of the main methods for tertiary oil recovery in oil fields with high water content. Partially hydrolyzed polyacrylamide is a high molecular polymer for polymer flooding with good performance, but the wastewater generated by oil recovery using partially hydrolyzed polyacrylamide is more difficult to treat because it contains partially hydrolyzed polyacrylamide. Existing treatment methods generally require multi-step treatment to achieve the treatment standard of oily wastewater containing partially hydrolyzed polyacrylamide. The treatment method is complicated and cumbersome, and the cost is relatively high. Therefore, it is urgent to develop a treatment method for oily wastewater containing partially hydrolyzed polyacrylamide with simple operating steps and good removal effect of partially hydrolyzed polyacrylamide. Summary of the invention

[0003] The purpose of the present invention is to provide a magnetic multi-functional titanium-coated iron amphiphilic particle and a preparation method thereof, so as to solve the technical problem that the treatment method of oily wastewater containing partially hydrolyzed polyacrylamide in the prior art is complicated and cumbersome.

[0004] To achieve the above object, the technical solution adopted by the present invention is:

[0005] In the first aspect, the present invention provides a magnetic multi-functional titanium-coated iron amphiphilic particle, comprising a magnetic Fe3O4 particle core and a titanium dioxide shell separated from the magnetic Fe3O4 particle core, the outer surface of the titanium dioxide shell comprising a hydrophilic part and a hydrophobic part, the inner surface of the titanium dioxide shell and the surface of the magnetic Fe3O4 particle core are grafted with polydiethylaminoethyl methacrylate (PDEAEMA), and the titanium dioxide shell has a micropore structure.

[0006] It should be noted that the "micropore structure" described in the present invention includes the intermolecular voids existing in the titanium dioxide macromolecular skeleton and the defects generated during the core-shell separation of the titanium dioxide shell from the magnetic Fe3O4 particle core, and even micropores and capillaries with a pore size of 0.5 to 50 nm.

[0007] The magnetic multi-functional titanium-coated iron amphiphilic particles provided by the present invention are coated with a titanium dioxide shell layer on the outside of the magnetic Fe3O4 particle core, which can protect the magnetic Fe3O4 particle core and resist corrosion of the magnetic Fe3O4 particle core by hydrochloric acid, sulfuric acid, nitric acid or various alkaline reagents within a certain period of time, so that the magnetic multi-functional titanium-coated iron amphiphilic particles can be used to treat acidic or alkaline wastewater.

[0008] The outer surface of the titanium dioxide shell of the magnetic multi-functional titanium-coated iron amphiphilic particles provided by the present invention includes both a hydrophilic part and a hydrophobic part, so that the magnetic multi-functional titanium-coated iron amphiphilic particles have amphiphilicity. Compared with traditional homogeneous particles, they have more stable emulsification properties and can emulsify oil and water phases more stably and widely to form a stable water-in-oil emulsion, providing a stability basis for the manipulation of emulsion droplets.

[0009] Moreover, the functional groups on the outer surface of the titanium dioxide shell of the magnetic multi-functional titanium-coated iron amphiphilic particles provided by the present invention have electrostatic and other interactions with partially hydrolyzed polyacrylamide, which promotes the adsorption of partially hydrolyzed polyacrylamide on the outer surface of the titanium dioxide shell. At the same time, after adsorption is achieved, the wetting effect of the internal structural composition of the amphiphilic particles on the partially hydrolyzed polyacrylamide adsorbed on the outer surface of the titanium dioxide shell will promote the adsorption process of partially hydrolyzed polyacrylamide into the titanium dioxide shell. The polydiethylaminoethyl methacrylate (PDEAEMA) grafted on the inner surface of the titanium dioxide shell and the surface of the core of the magnetic Fe3O4 particles forms a brush-like coating, which increases the specific surface area and enhances the hydrogen bond density. The micro-pore structure on the titanium dioxide shell provides a channel for the migration and transmission of partially hydrolyzed polyacrylamide, thereby achieving the adsorption and migration capture of partially hydrolyzed polyacrylamide by PDEAEMA. The magnetic multi-functional titanium-coated iron amphiphilic particles provided by the present invention greatly improve the adsorption capacity and efficiency of partially hydrolyzed polyacrylamide through the combination of internal and external structures.

[0010] In addition, PDEAEMA is pH-sensitive, showing hydrophilic properties at low pH values ​​and hydrophobic properties at high pH values. The pH sensitivity can be used to achieve repeated adsorption and desorption of PDEAEMA on partially hydrolyzed polyacrylamide, so that the magnetic multi-functional titanium-coated iron amphiphilic particles can be reused, greatly reducing the material cost of sewage treatment. Moreover, partially hydrolyzed polyacrylamide itself is weakly acidic, which is more conducive to the transfer adsorption of partially hydrolyzed polyacrylamide from the outer surface of the titanium dioxide shell to the PDEAEMA inside the titanium dioxide shell.

[0011] In addition, the used magnetic multi-functional titanium-coated iron amphiphilic particles can be washed and extracted with a benign solvent of partially hydrolyzed polyacrylamide (such as ethanol), which can also remove the adsorbed partially hydrolyzed polyacrylamide and achieve the reuse of the magnetic multi-functional titanium-coated iron amphiphilic particles.

[0012] According to some embodiments of the present invention, the hydrophilic portion is obtained by modifying the outer surface of the titanium dioxide shell layer with an amino-containing silane coupling agent.

[0013] According to some embodiments of the present invention, the amino-containing silane coupling agent includes 3-aminopropyltriethoxysilane.

[0014] 3-aminopropyltriethoxysilane modification is used to allow amino groups to exist on the hydrophilic part of the outer surface of the titanium dioxide shell, which can produce weak interactions with partially hydrolyzed polyacrylamide with carboxyl groups, thereby achieving adsorption of partially hydrolyzed polyacrylamide.

[0015] According to some embodiments of the present invention, the hydrophobic portion is obtained by modifying the outer surface of the titanium dioxide shell layer with an alkyl-containing silane coupling agent.

[0016] According to some embodiments of the present invention, the alkyl-containing silane coupling agent includes n-octyltriethoxysilane.

[0017] According to some embodiments of the present invention, the area of ​​the hydrophilic portion accounts for 1 / 3 to 2 / 3 of the total area of ​​the outer surface of the titanium dioxide shell layer.

[0018] According to some embodiments of the present invention, the particle size of the magnetic multi-functional titanium-coated iron amphiphilic particles is 100nm<r≤1000nm.

[0019] In a second aspect, the present invention provides a method for preparing magnetic multi-functional titanium-coated iron amphiphilic particles, comprising:

[0020] S1. Dispersing magnetic Fe3O4 particles and tetrabutyl titanate in an alcohol solvent to obtain titanium-coated iron magnetic particles;

[0021] S2. The titanium-coated iron magnetic particles are dispersed in water, paraffin is added, heated until the paraffin is completely melted, stirred and mixed, cooled and filtered to obtain paraffin balls formed by the titanium-coated iron magnetic particles embedded on the surface of the paraffin;

[0022] S3. The paraffin balls and the amino-containing silane coupling agent are stirred in dimethyl sulfoxide for reaction, and then the paraffin is removed from the obtained solid particles to obtain hydrophilic modified particles;

[0023] S4. The hydrophilic modified particles and the alkyl-containing silane coupling agent are stirred in ethanol to react to obtain amphiphilic modified particles;

[0024] S5. The amphiphilic modified particles are mixed with acetic acid for 8-12 hours to obtain core-shell separated amphiphilic modified particles;

[0025] S6. The core-shell separated amphiphilic modified particles are subjected to a modification reaction with 4-(chloromethyl)phenyltrimethoxysilane in an alcohol solvent; and then grafted with diethylaminoethyl methacrylate to obtain the magnetic multi-functional titanium-coated iron amphiphilic particles after the reaction is completed.

[0026] The preparation method of the magnetic multi-functional titanium-coated iron amphiphilic particles provided by the present invention first uses magnetic Fe3O4 particles as a carrier, uses tetrabutyl titanate to achieve hydrolysis on the surface of the magnetic Fe3O4 particles, and wraps the magnetic Fe3O4 particles with a titanium dioxide shell through a sol-gel process. Then, paraffin is used as the oil phase, and titanium-coated iron magnetic particles are used as solid particle emulsifiers. When the temperature is higher than the paraffin phase transition temperature, the oil-water phase is emulsified to form a stable water-in-paraffin emulsion. After the emulsion is cooled, the paraffin phase solidifies and separates from the water phase to obtain paraffin balls formed by the titanium-coated iron magnetic particles embedded in the paraffin surface, and the titanium-coated iron magnetic particles are partially embedded in the paraffin and partially exposed outside the paraffin. Then, the outer surface of the titanium-coated iron magnetic particles exposed outside the paraffin is hydrophilically modified; then the paraffin is removed to expose the part of the titanium-coated iron magnetic particles previously protected by the paraffin, and the outer surface of this part is hydrophobically modified to obtain amphiphilic particles whose particle surface includes both a hydrophilic part and a hydrophobic part. Then, an acid etching treatment is performed to reduce the size of the magnetic Fe3O4 particles, separate them from the titanium dioxide shell, and generate cavities between the core-shell structure. 4-(chloromethyl)phenyltrimethoxysilane is further used to modify the surface of the magnetic Fe3O4 particles and the inner surface of the titanium dioxide shell with benzyl chloride [4-(chloromethyl)phenyl]. Benzyl chloride is highly active and can be grafted with polydiethylaminoethyl methacrylate (PDEAEMA) through ATRP (atom transfer radical polymerization) reaction to obtain the magnetic multi-functional titanium-coated iron amphiphilic particles.

[0027] In the present invention, the titanium dioxide shell is used to wrap the magnetic Fe3O4 particles, which can resist the corrosion of hydrochloric acid, sulfuric acid, nitric acid or various alkaline reagents for a certain period of time, thereby ensuring the industrial application of the magnetic particles. In addition, the titanium dioxide shell in the present invention is a polymer formed by the hydrolysis and condensation of tetra-n-butyl titanate. Although the formed titanium dioxide shell is relatively dense, in the sol-gel process of the hydrolysis of tetra-n-butyl titanate, the macromolecular skeleton formed by the condensation reaction still has intermolecular gaps, thereby ensuring the smooth progress of the subsequent acid etching treatment, 4-(chloromethyl)phenyltrimethoxysilane modification and PDEAEMA grafting process.

[0028] In the present invention, after acid etching, the magnetic Fe3O4 particles are reduced and core-shell separation occurs. This process will further cause defects in the titanium dioxide shell, even micropores or capillaries. The micropore structure composed of the intermolecular gaps in the titanium dioxide shell provides a channel for the transmission and migration of partially hydrolyzed polyacrylamide to the inside of the titanium dioxide shell. The acid etching reagent uses acetic acid, which can make the etching slow, ensure that the etching process is controllable, and make the surface of the core of the magnetic Fe3O4 particles smoother; if hydrochloric acid, sulfuric acid, etc. are used, it is difficult to control the etching process, which can easily lead to excessive etching, thereby making the magnetic properties of the particles too weak or even completely disappear.

[0029] According to some embodiments of the present invention, the alcohol solvent includes at least one of methanol, ethanol, propanol, butanol, isopropanol, and cyclohexanol.

[0030] According to some embodiments of the present invention, the stirring and mixing speed in step S2 is 1000-5000 rpm.

[0031] In the present invention, the stirring speed in step S2 will directly affect the emulsification process of the particulate emulsifier (titanium-coated iron magnetic particles), and directly lead to the stabilization of the emulsion interface by the particulate emulsifier. When the stirring speed is less than 1000rpm, the stirring speed is too low, the particulate emulsifier is difficult to deliver to the interface, the interface cannot be stabilized, and the emulsion is easily broken; when the stirring speed is greater than 5000rpm, the stirring speed is too high, and the particulate emulsifier is forced to be pulled at the interface, which easily leads to interface instability and emulsion breaking. Therefore, in order to ensure emulsification and interface stability, it is advisable that the stirring speed in step S2 is controlled at 1000-5000rpm.

[0032] According to some embodiments of the present invention, the stirring and mixing time in step S2 is 3 to 5 minutes.

[0033] According to some embodiments of the present invention, the amino-containing silane coupling agent includes 3-aminopropyltriethoxysilane.

[0034] The outer surface of titanium-coated iron magnetic particles is locally hydrophilically modified by 3-aminopropyltriethoxysilane in dimethyl sulfoxide. The sol-gel composite is achieved on the outer surface of the titanium-coated iron magnetic particles exposed outside the paraffin wax through a hydrolysis process. Amino groups are modified on one side of the outer surface of the titanium-coated iron magnetic particles to achieve adsorption of partially hydrolyzed polyacrylamide.

[0035] According to some embodiments of the present invention, the alkyl-containing silane coupling agent includes n-octyltriethoxysilane.

[0036] The local hydrophobic modification of the outer surface of titanium-coated iron magnetic particles using n-octyltriethoxysilane is first performed by removing paraffin with an alcohol solvent, so that the protected part of the titanium-coated iron magnetic particles embedded in the paraffin is exposed, and then the part of the titanium-coated iron magnetic particles exposed from the embedded paraffin is hydrolyzed by n-octyltriethoxysilane to achieve surface sol-gel composite, and n-octyl groups are modified on the other side of the outer surface of the titanium-coated iron magnetic particles.

[0037] According to some embodiments of the present invention, the mass ratio of the magnetic Fe3O4 particles to tetrabutyl titanate is 1:(0.1-1).

[0038] According to some embodiments of the present invention, the mass ratio of the magnetic Fe3O4 particles to paraffin is 1:(10-200).

[0039] According to some embodiments of the present invention, the mass ratio of paraffin wax to water is 1:(2-10).

[0040] According to some embodiments of the present invention, the mass ratio of the magnetic Fe3O4 particles to the amino-containing silane coupling agent is 1:(0.001-0.01).

[0041] According to some embodiments of the present invention, the mass ratio of the magnetic Fe3O4 particles to the alkyl-containing silane coupling agent is 1:(0.001-0.01).

[0042] According to some embodiments of the present invention, the mass ratio of the magnetic Fe3O4 particles to 4-(chloromethyl)phenyltrimethoxysilane is 1:(0.001-0.01).

[0043] According to some embodiments of the present invention, the mass ratio of the magnetic Fe3O4 particles to diethylaminoethyl methacrylate is 1:(0.02-0.1).

[0044] According to some embodiments of the present invention, the particle size of the magnetic Fe3O4 particles is 100-500 nm.

[0045] According to some embodiments of the present invention, the particle size ratio of the magnetic Fe3O4 particles to the core of the magnetic Fe3O4 particles is 100:(10-99).

[0046] In the present invention, if the particle size ratio of the magnetic Fe3O4 particles to the magnetic Fe3O4 particle core is less than 100:99, it means that the gap between the titanium dioxide shell and the magnetic Fe3O4 particle core is too small, which will affect the adsorption capacity of the magnetic multi-performance titanium-coated iron amphiphilic particles to partially hydrolyzed polyacrylamide; if the particle size ratio of the magnetic Fe3O4 particles to the magnetic Fe3O4 particle core is greater than 100:10, it means that the size of the magnetic Fe3O4 particle core is too small, which will lead to serious magnetic attenuation and difficulty in achieving magnetic manipulation of the external magnetic field.

[0047] According to some embodiments of the present invention, the grafting reaction includes: dissolving cuprous chloride and 2,2-bipyridine in a solvent, adding amphiphilic modified particles treated by the modification reaction and diethylaminoethyl methacrylate, and stirring the reaction in a nitrogen atmosphere at 60-100°C.

[0048] According to some embodiments of the present invention, the solvent used in the grafting reaction includes at least one of water, tetrahydrofuran (THF), and N,N-dimethylformamide (DMF).

[0049] According to some embodiments of the present invention, the stirring reaction time in step S3 is 5 to 6 hours.

[0050] According to some embodiments of the present invention, the stirring reaction time in step S4 is 5 to 6 hours.

[0051] According to some embodiments of the present invention, the magnetic Fe3O4 particles and tetrabutyl titanate are dispersed in an alcohol solvent by ultrasound and stirring for 12 to 24 hours. Preferably, the ultrasound frequency is 60 to 80 Hz and / or the stirring speed is 50 to 100 rpm.

[0052] According to some embodiments of the present invention, the titanium-coated ferromagnetic particles are dispersed in water by ultrasound and stirring. Preferably, the ultrasound frequency is 60-80 Hz and / or the stirring speed is 50-100 rpm.

[0053] According to some embodiments of the present invention, the paraffin balls are dispersed in dimethyl sulfoxide by stirring, and preferably, the stirring speed is 50 to 100 rpm;

[0054] According to some embodiments of the present invention, the hydrophilic modified particles are dispersed in the alcohol solvent by ultrasound and stirring. Preferably, the ultrasound frequency is 60-80 Hz and / or the stirring speed is 200-300 rpm.

[0055] According to some embodiments of the present invention, mixing the amphiphilic modified particles with acetic acid for 8-12 hours comprises: dispersing the amphiphilic modified particles in water, adding acetic acid, and mixing for 8-12 hours by ultrasound and stirring. Preferably, the ultrasound frequency is 60-80 Hz and / or the stirring speed is 50-100 rpm.

[0056] In a third aspect, the present invention provides a magnetic multi-functional titanium-coated iron amphiphilic particle prepared by the preparation method described in the second aspect.

[0057] In a fourth aspect, the present invention provides the use of the magnetic multi-functional titanium-coated iron amphiphilic particles described in the first aspect or the magnetic multi-functional titanium-coated iron amphiphilic particles described in the third aspect in the treatment of oily wastewater containing partially hydrolyzed polyacrylamide.

[0058] The beneficial effects of the present invention are at least:

[0059] (1) The magnetic multi-functional titanium-coated iron amphiphilic particles provided by the present invention have a wide size distribution window, can achieve submicron / micron distribution, and have uniform particle size.

[0060] (2) The magnetic multi-functional titanium-coated iron amphiphilic particles provided by the present invention have excellent emulsification properties. The droplets stabilized by the emulsification using the magnetic multi-functional titanium-coated iron amphiphilic particles can be manipulated by an external magnetic field to achieve the enrichment and migration of oil droplets, thereby achieving oil-water separation. At the same time, they also have selective adsorption characteristics and can selectively adsorb partially hydrolyzed polyacrylamide, thereby efficiently treating oil-containing wastewater containing partially hydrolyzed polyacrylamide in one step.

[0061] (3) The magnetic multi-functional titanium-coated iron amphiphilic particles provided by the present invention can realize repeated adsorption and desorption of partially hydrolyzed polyacrylamide, so that the magnetic multi-functional titanium-coated iron amphiphilic particles can be reused many times, and the adsorption capacity for partially hydrolyzed polyacrylamide will not show a significant decrease, which can greatly reduce the material cost of sewage treatment.

[0062] (4) The magnetic multi-functional titanium-coated iron amphiphilic particles provided by the present invention have a structure in which a titanium dioxide shell covers the magnetic Fe3O4 particle core, which can protect the magnetic Fe3O4 particle core and effectively improve the acid and alkali resistance of the amphiphilic particles, so that it can be used to treat sewage with more complex composition.

[0063] (5) The preparation method of the magnetic multi-functional titanium-coated iron amphiphilic particles provided by the present invention has a simple process, low cost and readily available raw materials, and can achieve industrial mass production at the ton level. DETAILED DESCRIPTION

[0064] In order to make the technical problems, technical solutions and beneficial effects to be solved by the present invention more clearly understood, the present invention is further described in detail below in conjunction with specific embodiments. It should be understood that the specific embodiments described herein are only used to explain this patent in detail and do not limit the scope of protection of the present invention in any way.

[0065] Unless otherwise defined, the technical terms used in the following examples have the same meanings as those generally understood by those skilled in the art to which the present invention belongs. The reagents used in the following examples, unless otherwise specified, are all conventional biochemical reagents; the raw materials, instruments and equipment used in the following examples, etc., can all be purchased on the market or can be obtained by existing methods; the reagent amounts, unless otherwise specified, are the reagent amounts used in conventional experimental operations; the experimental methods, unless otherwise specified, are all conventional methods.

[0066] Example 1

[0067] S1. Disperse 4.0 g of magnetic Fe3O4 particles (particle size of 0.2 μm) in 350 mL of ethanol, add 2 g of tetrabutyl titanate, add 80 Hz ultrasound and 60 rpm overhead stirring, maintain ultrasound and stirring to promote the dispersion of magnetic Fe3O4 particles, continue for 12 hours, and separate titanium-coated iron magnetic particles.

[0068] S2. Disperse the titanium-coated iron magnetic particles into 400mL of water, and add 80Hz ultrasound and 60rpm overhead stirring at the same time, and maintain ultrasound and stirring to promote the dispersion of the titanium-coated iron magnetic particles. Raise the water temperature to 80°C, add 40g of paraffin (phase transition temperature is 52°C), and continue stirring until the paraffin is completely melted. Turn off the ultrasound and increase the stirring speed to 2000rpm, and continue stirring for 3min. Stop stirring and heating, cool the sample to room temperature, filter out the solidified paraffin balls, and separate them from the water. Disperse the paraffin balls on filter paper and dry naturally to obtain paraffin ball powder formed by the titanium-coated iron magnetic particles embedded in the paraffin surface.

[0069] S3. Disperse the paraffin ball powder in 200 mL of dimethyl sulfoxide, and stir the dispersion slowly with an overhead stirrer at a speed of 80 rpm. Add 40 mg of 3-aminopropyltriethoxysilane to the dispersion and continue stirring for 6 hours. Use an external magnetic field to separate the paraffin ball powder and the solvent, and dry the paraffin ball powder in a natural state. Disperse the paraffin ball powder in 200 mL of ethanol, dissolve the paraffin, and separate the solid particles using an external magnetic field to obtain Fe3O4@TiO2-NH2 particles with amino groups modified on one side of the surface.

[0070] S4. Disperse Fe3O4@TiO2-NH2 particles in 200 mL of ethanol, stir the dispersion with an overhead stirrer at 300 rpm, and apply 80 Hz ultrasound. Add 40 mg of n-octylpropyltriethoxysilane to the dispersion and continue stirring for 6 h. Separate the solid particles using an external magnetic field to obtain C8-Fe3O4@TiO2-NH2 particles.

[0071] S5. The C8-Fe3O4@TiO2-NH2 particles were dispersed in 200 mL of water, 5 mL of acetic acid was added, and the dispersion was stirred for 10 h using an overhead stirrer at a speed of 60 rpm, while 80 Hz ultrasound was applied to obtain core-shell separated C8-Fe3O4@TiO2-NH2 particles;

[0072] S6. Disperse the core-shell separated C8-Fe3O4@TiO2-NH2 particles in 200 mL of ethanol, add 20 mg of 4-(chloromethyl)phenyltrimethoxysilane, and stir at 60 rpm for 12 h to obtain modified C8-Fe3O4@TiO2-NH2 particles; dissolve 0.04 g of cuprous chloride and 0.04 g of 2,2-bipyridine in 100 mL of DMF, add the above-mentioned modified C8-Fe3O4@TiO2-NH2 particles, and add 0.2 g of DEAEMA, and introduce N2 to deoxygenate for 30 min. Heat to 80 ° C, stir at 100 rpm for 3 h, and obtain magnetic multi-functional titanium-coated iron amphiphilic particles after the reaction.

[0073] Example 2

[0074] S1. Disperse 4.0 g of magnetic Fe3O4 particles (particle size of 0.2 μm) in 350 mL of ethanol, add 4 g of tetrabutyl titanate, add 80 Hz ultrasound and 60 rpm overhead stirring, maintain ultrasound and stirring to promote the dispersion of magnetic Fe3O4 particles, continue for 12 hours, and separate titanium-coated iron magnetic particles.

[0075] S2. Disperse the titanium-coated iron magnetic particles into 400mL of water, and add 80Hz ultrasound and 60rpm overhead stirring at the same time, and maintain ultrasound and stirring to promote the dispersion of the titanium-coated iron magnetic particles. Raise the water temperature to 80°C, add 40g of paraffin (phase transition temperature is 52°C), and continue stirring until the paraffin is completely melted. Turn off the ultrasound and increase the stirring speed to 1000rpm, and continue stirring for 5min. Stop stirring and heating, cool the sample to room temperature, filter out the solidified paraffin balls, and separate them from the water. Disperse the paraffin balls on filter paper and dry naturally to obtain paraffin ball powder formed by the titanium-coated iron magnetic particles embedded in the paraffin surface.

[0076] S3. Disperse the paraffin ball powder in 200 mL of dimethyl sulfoxide, and use an overhead stirrer to slowly stir the dispersion at a speed of 80 rpm. Add 5 mg of 3-aminopropyltriethoxysilane to the dispersion and continue stirring for 6 hours. Use an external magnetic field to separate the paraffin ball powder and the solvent, and dry the paraffin ball powder in a natural state. Disperse the paraffin ball powder in 200 mL of ethanol, dissolve the paraffin, and use an external magnetic field to separate the solid particles to obtain Fe3O4@TiO2-NH2 particles with amino groups modified on one side of the surface.

[0077] S4. Disperse Fe3O4@TiO2-NH2 particles in 200 mL of ethanol, stir the dispersion with an overhead stirrer at 300 rpm, and apply 80 Hz ultrasound. Add 5 mg of n-octylpropyltriethoxysilane to the dispersion and continue stirring for 6 h. Separate the solid particles using an external magnetic field to obtain C8-Fe3O4@TiO2-NH2 particles.

[0078] S5. The C8-Fe3O4@TiO2-NH2 particles were dispersed in 200 mL of water, 5 mL of acetic acid was added, and the dispersion was stirred for 10 h using an overhead stirrer at a speed of 60 rpm, while 80 Hz ultrasound was applied to obtain core-shell separated C8-Fe3O4@TiO2-NH2 particles;

[0079] S6. Disperse the core-shell separated C8-Fe3O4@TiO2-NH2 particles in 200 mL of ethanol, add 30 mg of 4-(chloromethyl)phenyltrimethoxysilane, and stir at 60 rpm for 12 h to obtain modified C8-Fe3O4@TiO2-NH2 particles; dissolve 0.04 g of cuprous chloride and 0.04 g of 2,2-bipyridine in 100 mL of DMF, add the above-mentioned modified C8-Fe3O4@TiO2-NH2 particles, and add 0.1 g of DEAEMA. At the same time, introduce N2 to deoxygenate for 30 min, heat to 80 ° C, stir at 100 rpm for 3 h, and after the reaction, obtain magnetic multi-functional titanium-coated iron amphiphilic particles.

[0080] Example 3

[0081] S1. Disperse 4.0 g of magnetic Fe3O4 particles (particle size of 0.2 μm) in 350 mL of ethanol, add 0.5 g of tetrabutyl titanate, add 80 Hz ultrasound and 60 rpm overhead stirring, maintain ultrasound and stirring to promote the dispersion of magnetic Fe3O4 particles, continue for 12 hours, and separate titanium-coated iron magnetic particles.

[0082] S2. Disperse the titanium-coated iron magnetic particles into 600mL of water, and add 80Hz ultrasound and 60rpm overhead stirring at the same time, and maintain ultrasound and stirring to promote the dispersion of the titanium-coated iron magnetic particles. Raise the water temperature to 80°C, add 100g of paraffin wax (phase transition temperature is 52°C), and continue stirring until the paraffin wax is completely melted. Turn off the ultrasound and increase the stirring speed to 5000rpm, and continue stirring for 4min. Stop stirring and heating, cool the sample to room temperature, filter out the solidified paraffin balls, and separate them from the water. Disperse the paraffin balls on filter paper and dry naturally to obtain paraffin ball powder formed by the titanium-coated iron magnetic particles embedded in the paraffin surface.

[0083] S3. Disperse the paraffin ball powder in 200 mL of dimethyl sulfoxide, and use an overhead stirrer to slowly stir the dispersion at a speed of 80 rpm. Add 20 mg of 3-aminopropyltriethoxysilane to the dispersion and continue stirring for 6 hours. Use an external magnetic field to separate the paraffin ball powder and the solvent, and dry the paraffin ball powder in a natural state. Disperse the paraffin ball powder in 200 mL of ethanol, dissolve the paraffin, and use an external magnetic field to separate the solid particles to obtain Fe3O4@TiO2-NH2 particles with amino groups modified on one side of the surface.

[0084] S4. Disperse Fe3O4@TiO2-NH2 particles in 200 mL of ethanol, stir the dispersion with an overhead stirrer at 300 rpm, and apply 80 Hz ultrasound. Add 20 mg of n-octylpropyltriethoxysilane to the dispersion and continue stirring for 6 h. Separate the solid particles using an external magnetic field to obtain C8-Fe3O4@TiO2-NH2 particles.

[0085] S5. The C8-Fe3O4@TiO2-NH2 particles were dispersed in 200 mL of water, 5 mL of acetic acid was added, and the dispersion was stirred for 10 h using an overhead stirrer at a speed of 60 rpm, while 80 Hz ultrasound was applied to obtain core-shell separated C8-Fe3O4@TiO2-NH2 particles;

[0086] S6. Disperse the core-shell separated C8-Fe3O4@TiO2-NH2 particles in 200 mL of ethanol, add 10 mg of 4-(chloromethyl)phenyltrimethoxysilane, and stir at 60 rpm for 12 h to obtain modified C8-Fe3O4@TiO2-NH2 particles; dissolve 0.04 g of cuprous chloride and 0.04 g of 2,2-bipyridine in 100 mL of DMF, add the above-mentioned modified C8-Fe3O4@TiO2-NH2 particles, and add 0.4 g of DEAEMA, and introduce N2 to deoxygenate for 30 min. Heat to 80 ° C, stir at 100 rpm for 3 h, and obtain magnetic multi-functional titanium-coated iron amphiphilic particles after the reaction.

[0087] Example 4

[0088] S1. Disperse 4.0 g of magnetic Fe3O4 particles (particle size of 0.2 μm) in 350 mL of ethanol, add 2 g of tetrabutyl titanate, add 80 Hz ultrasound and 60 rpm overhead stirring, maintain ultrasound and stirring to promote the dispersion of magnetic Fe3O4 particles, continue for 12 hours, and separate titanium-coated iron magnetic particles.

[0089] S2. Disperse the titanium-coated iron magnetic particles into 400 mL of water, and add 80 Hz ultrasound and 60 rpm overhead stirring at the same time, and maintain ultrasound and stirring to promote the dispersion of the titanium-coated iron magnetic particles. Raise the water temperature to 80 ° C, add 40 g of paraffin (phase transition temperature is 52 ° C), and continue stirring until the paraffin is completely melted. Turn off the ultrasound and increase the stirring speed to 500 rpm. Because the stirring speed is too low, the particles cannot be delivered to the oil-water interface by mechanical force, the titanium-coated iron magnetic particles cannot be stabilized at the oil-water interface, the oil-water two phases cannot be stably emulsified, the water phase and the oil phase are still two phases, and the paraffin ball powder formed by the titanium-coated iron magnetic particles embedded in the paraffin surface cannot be obtained.

[0090] Example 5

[0091] S1. Disperse 4.0 g of magnetic Fe3O4 particles (particle size of 0.2 μm) in 350 mL of ethanol, add 2 g of tetrabutyl titanate, add 80 Hz ultrasound and 60 rpm overhead stirring, maintain ultrasound and stirring to promote the dispersion of magnetic Fe3O4 particles, continue for 12 hours, and separate titanium-coated iron magnetic particles.

[0092] S2. Disperse the titanium-coated iron magnetic particles into 400mL of water, and add 80Hz ultrasound and 60rpm overhead stirring at the same time, and maintain ultrasound and stirring to promote the dispersion of the titanium-coated iron magnetic particles. Raise the water temperature to 80°C, add 40g paraffin (phase transition temperature is 52°C), and continue stirring until the paraffin is completely melted. Turn off the ultrasound and increase the stirring speed to 6000rpm. Due to the high stirring speed, although the titanium-coated iron magnetic particles are mechanically delivered to the oil-water interface for emulsification, the excessively fast mechanical stirring causes the particles to peel off at the interface, making the interface unstable, and demulsification occurs, and the paraffin ball powder formed by the titanium-coated iron magnetic particles embedded in the paraffin surface cannot be obtained.

[0093] Comparative Example 1

[0094] S1. Disperse 4.0 g of magnetic Fe3O4 particles (particle size of 0.2 μm) in 350 mL of ethanol, add 2 g of tetrabutyl titanate, add 80 Hz ultrasound and 60 rpm overhead stirring, maintain ultrasound and stirring to promote the dispersion of magnetic Fe3O4 particles, continue for 12 hours, and separate titanium-coated iron magnetic particles.

[0095] S2. Disperse the titanium-coated iron magnetic particles into 400mL of water, and add 80Hz ultrasound and 60rpm overhead stirring at the same time, and maintain ultrasound and stirring to promote the dispersion of the titanium-coated iron magnetic particles. Raise the water temperature to 80°C, add 40g of paraffin (phase transition temperature is 52°C), and continue stirring until the paraffin is completely melted. Turn off the ultrasound and increase the stirring speed to 2000rpm, and continue stirring for 3min. Stop stirring and heating, cool the sample to room temperature, filter out the solidified paraffin balls, and separate them from the water. Disperse the paraffin balls on filter paper and dry naturally to obtain paraffin ball powder formed by the titanium-coated iron magnetic particles embedded in the paraffin surface.

[0096] S3. Disperse the paraffin ball powder in 200 mL of dimethyl sulfoxide, and stir the dispersion slowly with an overhead stirrer at a speed of 80 rpm. Add 40 mg of 3-aminopropyltriethoxysilane to the dispersion and continue stirring for 6 hours. Use an external magnetic field to separate the paraffin ball powder and the solvent, and dry the paraffin ball powder in a natural state. Disperse the paraffin ball powder in 200 mL of ethanol, dissolve the paraffin, and separate the solid particles using an external magnetic field to obtain Fe3O4@TiO2-NH2 particles with amino groups modified on one side of the surface.

[0097] S4. Disperse Fe3O4@TiO2-NH2 particles in 200 mL of ethanol, stir the dispersion with an overhead stirrer at 300 rpm, and apply 80 Hz ultrasound. Add 40 mg of n-octylpropyltriethoxysilane to the dispersion and continue stirring for 6 h. Separate the solid particles using an external magnetic field to obtain particles.

[0098] Comparative Example 2

[0099] S1. Disperse 4.0 g of magnetic Fe3O4 particles (particle size of 0.2 μm) in 350 mL of ethanol, add 2 g of tetrabutyl titanate, add 80 Hz ultrasound and 60 rpm overhead stirring, maintain ultrasound and stirring to promote the dispersion of magnetic Fe3O4 particles, continue for 12 hours, and separate titanium-coated iron magnetic particles.

[0100] S2. The titanium-coated iron magnetic particles were dispersed in 200 mL of water, 5 mL of acetic acid was added, and the dispersion was stirred for 10 h using an overhead stirrer at a speed of 60 rpm, while additionally applying 80 Hz ultrasound to obtain core-shell separated titanium-coated iron magnetic particles;

[0101] S3. The core-shell separated titanium-coated ferromagnetic particles were dispersed in 200 mL of ethanol, 20 mg of 4-(chloromethyl)phenyltrimethoxysilane was added, and the mixture was stirred at 60 rpm for 12 h to obtain modified titanium-coated ferromagnetic particles; 0.04 g of cuprous chloride and 0.04 g of 2,2-bipyridine were dissolved in 100 mL of DMF, the modified titanium-coated ferromagnetic particles were added, and 0.2 g of DEAEMA was added. N2 was introduced for deoxygenation for 30 min, the temperature was raised to 80 ° C, and the mixture was stirred at 100 rpm for 3 h. After the reaction, the particles were obtained.

[0102] Comparative Example 3

[0103] The particles were prepared by referring to the preparation method of Example 1, except that the acetic acid was replaced by an equal volume of dilute hydrochloric acid (pH 6).

[0104] Comparative Example 4

[0105] The particles were prepared by referring to the preparation method of Example 1, except that acetic acid was replaced by an equal volume of sulfuric acid.

[0106] Performance Evaluation

[0107] (I) The particle size of the particles of each embodiment and comparative example was measured using a scanning electron microscope, and the results are shown in the following table:

[0108] Group Particle size (nm) Example 1 240 Example 2 280 Example 3 210 Comparative Example 1 240 Comparative Example 2 240 Comparative Example 3 240 Comparative Example 4 240

[0109] (II) Wastewater treatment effect

[0110] 1 kg of the particles prepared in each embodiment and comparative example were added to 10 t of partially hydrolyzed polyacrylamide oily wastewater (COD value was 2020, petroleum pollutant content was 52.3 mg / L, and partially hydrolyzed polyacrylamide content was 103.05 mg / L), and the oily wastewater was emulsified by stirring at a speed of 1000 rpm for 1 min using a shearing machine; then the migration and enrichment of the emulsified oil droplets of the magnetic particles were achieved by controlling the external magnetic field. The treated wastewater was tested, and the test method is shown in the following table:

[0111]

[0112] The test results are shown in the following table:

[0113]

[0114] (III) Cyclic performance

[0115] The magnetic multi-functional titanium-coated iron amphiphilic particles of Example 1 are regenerated. The specific method includes: collecting the magnetic multi-functional titanium-coated iron amphiphilic particles of Example 1 after wastewater treatment, washing with ethanol, the mass ratio of ethanol to amphiphilic particles is 10:1, and then freeze-drying after washing to obtain regenerated particles.

[0116] The regenerated particles were used to repeat the treatment process of partially hydrolyzed polyacrylamide-containing oily wastewater in step (ii), and the indicators of the treated wastewater were similar to the treatment effect of the first wastewater treatment using the magnetic multi-functional titanium-coated iron-amphiphilic particles in Example 1. The magnetic multi-functional titanium-coated iron-amphiphilic particles can be recycled for more than 100 times, and the removal effect of COD, petroleum and partially hydrolyzed polyacrylamide will not be significantly deteriorated.

[0117] It should be noted that the embodiments described above are only used to explain the present invention and do not constitute any limitation to the present invention. The present invention has been described with reference to typical embodiments, but it should be understood that the words used therein are descriptive and explanatory words, rather than restrictive words. The present invention may be modified as specified within the scope of the claims of the present invention, and the present invention may be revised without departing from the scope and spirit of the present invention. Although the present invention described therein relates to specific methods, materials and embodiments, it does not mean that the present invention is limited to the specific examples disclosed therein, on the contrary, the present invention can be extended to all other methods and applications with the same functions.

Claims

1. A magnetic multi-functional titanium-coated iron amphiphilic particle, characterized in that: It comprises a magnetic Fe3O4 particle core and a titanium dioxide shell separated from the magnetic Fe3O4 particle core. The outer surface of the titanium dioxide shell comprises a hydrophilic part and a hydrophobic part. The inner surface of the titanium dioxide shell and the surface of the magnetic Fe3O4 particle core are grafted with polydiethylaminoethyl methacrylate. The titanium dioxide shell has a microporous structure.

2. The magnetic multi-functional titanium-coated iron amphiphilic particles according to claim 1, characterized in that: The hydrophilic part is obtained by modifying the outer surface of the titanium dioxide shell layer with an amino-containing silane coupling agent; preferably, the amino-containing silane coupling agent includes 3-aminopropyltriethoxysilane; And / or, the hydrophobic part is obtained by modifying the outer surface of the titanium dioxide shell layer with an alkyl-containing silane coupling agent; preferably, the alkyl-containing silane coupling agent includes n-octyltriethoxysilane; And / or, the particle size of the magnetic multi-functional titanium-coated iron amphiphilic particles is 100nm<r≤1000nm.

3. A method for preparing magnetic multi-functional titanium-coated iron amphiphilic particles, characterized in that: include: S1. Dispersing magnetic Fe3O4 particles and tetrabutyl titanate in an alcohol solvent to obtain titanium-coated iron magnetic particles; S2. The titanium-coated iron magnetic particles are dispersed in water, paraffin is added, heated until the paraffin is completely melted, stirred and mixed, cooled and filtered to obtain paraffin balls formed by the titanium-coated iron magnetic particles embedded in the surface of the paraffin; S3. The paraffin balls and the amino-containing silane coupling agent are stirred in dimethyl sulfoxide for reaction, and then the paraffin is removed from the obtained solid particles to obtain hydrophilic modified particles; S4. The hydrophilic modified particles and the alkyl-containing silane coupling agent are stirred in ethanol to react to obtain amphiphilic modified particles; S5. The amphiphilic modified particles are mixed with acetic acid for 8-12 hours to obtain core-shell separated amphiphilic modified particles; S6. The core-shell separated amphiphilic modified particles are subjected to a modification reaction with 4-(chloromethyl)phenyltrimethoxysilane in an alcohol solvent; and then grafted with diethylaminoethyl methacrylate to obtain the magnetic multi-functional titanium-coated iron amphiphilic particles after the reaction is completed.

4. The preparation method according to claim 3, characterized in that: The stirring and mixing speed in step S2 is 1000-5000 rpm.

5. The preparation method according to claim 3 or 4, characterized in that: The amino-containing silane coupling agent includes 3-aminopropyltriethoxysilane; And / or, the alkyl-containing silane coupling agent includes n-octyltriethoxysilane.

6. The preparation method according to any one of claims 3 to 5, characterized in that: The mass ratio of the magnetic Fe3O4 particles to tetrabutyl titanate is 1:(0.1-1); and / or, the mass ratio of the magnetic Fe3O4 particles to paraffin is 1:(10-200); And / or, the mass ratio of the magnetic Fe3O4 particles to the amino-containing silane coupling agent is 1:(0.001-0.01); And / or, the mass ratio of the magnetic Fe3O4 particles to the alkyl-containing silane coupling agent is 1:(0.001-0.01); and / or, the mass ratio of the magnetic Fe3O4 particles to 4-(chloromethyl)phenyltrimethoxysilane is 1:(0.001-0.01); And / or, the mass ratio of the magnetic Fe3O4 particles to diethylaminoethyl methacrylate is 1:(0.02-0.1).

7. The preparation method according to any one of claims 3 to 6, characterized in that: The particle size of the magnetic Fe3O4 particles is 100 to 500 nm; And / or, the particle size ratio of the magnetic Fe3O4 particles to the core of the magnetic Fe3O4 particles is 100:(10-99).

8. The preparation method according to any one of claims 3 to 7, characterized in that: The grafting reaction comprises: dissolving cuprous chloride and 2,2-bipyridine in a solvent, adding amphiphilic modified particles treated by the modification reaction and diethylaminoethyl methacrylate, and stirring the reaction under a nitrogen atmosphere at 60-100° C.

9. A magnetic multi-functional titanium-coated iron amphiphilic particle prepared by the preparation method described in any one of claims 3-8.

10. Use of the magnetic multifunctional titanium-coated iron amphiphilic particles according to claim 1 or 2 or the magnetic multifunctional titanium-coated iron amphiphilic particles according to claim 9 in the treatment of oily wastewater containing partially hydrolyzed polyacrylamide.

Citation Information

Patent Citations

  • Hollow silica submicro-sphere with ferroferric oxide particle and silica core, and preparation method thereof

    CN104069513A

  • Amphiphilic and magnetic nano-particles and preparation method thereof

    CN110211757A

  • Mesoporous Janus nanosheet emulsifier with pH responsiveness as well as preparation method and application thereof

    CN111298711A

  • PH-responsive composite Janus nanoparticles and preparation method thereof

    CN114644823A

  • Spherical nanoparticles consisting of yolk-shell type single gold nanodot core and silica shell and synthesis method thereof

    KR101465440B1

Cited By

  • Static-conductive regenerated polypropylene composite material for petroleum delivery pipeline and preparation method of static-conductive regenerated polypropylene composite material

    CN121851547A